BIM as Evaluation Tool for Existing Building Energy and Quantities Takeoff - M. Abd, Abbas; Khamees, Alaa Sameer (Civil Engineering Journal, 2017)
Information technology and its application have resulted in enormous development in the construction industry during the last decade. The main reason behind this evolution was the incorporation of Building Information Modeling (BIM) to be an inefficient construction approach. BIM is now globally considered to be the tool of transforming the construction process to new era. It is also considered as a good tool for the whole project lifecycle. The aim of the present study is to clarify how BIM can be used in after project construction within uncertainty and risky environment such as document losses and unrecorded change orders. Interviews with project team, project site photography, collecting the available schemes and documents were the approaches used in this work to re-build the projects models. The results obtained from this work show that the knowledge and expectations of BIM within existing building have an admirable achievements for construction industry. Furthermore, BIM approach used in this work made more progress in the implementation of BIM as a rehabilitation and renovation tool in civil projects. The conclusions from this study reflect high correlation between the quantities take off with what as-built constructed, more than the traditional approach. The glamorous lessons derived from BIM implementation for the case study is; working with a model in which all project team feel comfortable and harmonic, will ensure enough resources to make the model updated and ought to lead to a minimum conflict within the model or what traditionally calledÂ  âproject documentsâ.